2023
DOI: 10.1113/jp284675
|View full text |Cite
|
Sign up to set email alerts
|

Increased pyramidal and VIP neuronal excitability in rat primary auditory cortex directly correlates with tinnitus behaviour

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…Ghimere et al ( 2023), provided the physiology/ pathology basis for the present study, included recordings from ENT rats (Ghimire et al, 2023). ENT animals were not included in the present study since for the tinnitus-related functional changes tested in the present study, ENT A1 neurons' PN group data from Ghimire et al (2023) found no statistical differences in physiological characteristics between ENT and control animals. A total of 24 Control and 18 tinnitus animals were used for in vitro studies as detailed in Table 1.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Ghimere et al ( 2023), provided the physiology/ pathology basis for the present study, included recordings from ENT rats (Ghimire et al, 2023). ENT animals were not included in the present study since for the tinnitus-related functional changes tested in the present study, ENT A1 neurons' PN group data from Ghimire et al (2023) found no statistical differences in physiological characteristics between ENT and control animals. A total of 24 Control and 18 tinnitus animals were used for in vitro studies as detailed in Table 1.…”
Section: Resultsmentioning
confidence: 86%
“…Exposed animals that showed control-like psychophysical behavior, with near control ability to distinguish silence from tone, were categorized as ENT ( Figsures 2B,C ) ( F (1, 75) = 2.6, p = 0.11, Two-way ANOVA, followed by a Bonferroni post-hoc test). Ghimere et al (2023), provided the physiology/pathology basis for the present study, included recordings from ENT rats ( Ghimire et al, 2023 ). ENT animals were not included in the present study since for the tinnitus-related functional changes tested in the present study, ENT A1 neurons’ PN group data from Ghimire et al (2023) found no statistical differences in physiological characteristics between ENT and control animals.…”
Section: Resultsmentioning
confidence: 99%